THE ANALYSIS OF FLOUTING MAXIM IN COOPERATIVE PRINCIPLE BY THE CHARACTERS IN JUMANJI: WELCOME TO THE JUNGLE MOVIE (2017) - Dunggio, Siti Anggriani; Ali, Sri Widyarti; Danial, Haris (Reduplikasi: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2025)
This research aims to find the types of flouting maxim that appear in the Jumanji: Welcome to the Jungle movie. The method used in this study is a qualitative descriptive method, used to explain in depth about the flouting maxim. The data were taken from conversations in the Jumanji: Welcome to the Jungle movie by watching it repeatedly. In this research, the researcher used the theory of Grice (1975) to analyze the types of flouting maxim, which consist of four types of maxims, namely the maxim of quantity, the maxim of quality, the maxim of relevance, and the maxim of manner. The results of this research indicate that the four types of flouting maxim appear during the conversation in the movie. Among the types of flouting maxim, the dominant data that appears in this research is the flouting the maxim of relevance. Meanwhile, the flouting maxim that occurs least frequently is the maxim of quality. There is one uniqueness found in this research that is not in Grice's theory but is found in the data. There is a hyperbolic metaphor in the flouting the maxim of manner by one of the characters in the movie.This research aims to find the types of flouting maxim that appear in the Jumanji: Welcome to the Jungle movie. The method used in this study is a qualitative descriptive method, used to explain in depth about the flouting maxim. The data were taken from conversations in the Jumanji: Welcome to the Jungle movie by watching it repeatedly. In this research, the researcher used the theory of Grice (1975) to analyze the types of flouting maxim, which consist of four types of maxims, namely the maxim of quantity, the maxim of quality, the maxim of relevance, and the maxim of manner. The results of this research indicate that the four types of flouting maxim appear during the conversation in the movie. Among the types of flouting maxim, the dominant data that appears in this research is the flouting the maxim of relevance. Meanwhile, the flouting maxim that occurs least frequently is the maxim of quality. There is one uniqueness found in this research that is not in Grice's theory but is found in the data. There is a hyperbolic metaphor in the flouting the maxim of manner by one of the characters in the movie.